Employer branding in the healthcare sector: The role of instrumental and symbolic image attributes among potential applicants and doctors - Luo, J.; Ferreira, A. I.; Lievens, F.; Trigo, B. R. (Journal of Chinese Human Resource Management, 2023)
This study draws from the instrumental-symbolic framework to analyze the employer image of public hospitals among final-year students and employed doctors. We examine the relative importance of perceived instrumental and symbolic employer image attributes in public hospitals in China among two groups of individuals (211 final-year students and 200 currently employed doctors). Both instrumental and symbolic attributes are significantly related to hospitals' attractiveness as an employer. Symbolic trait inferences explain incremental variance in employer attraction beyond instrumental attributes. Although both attributes explain similar portions of the variance in the two groups, the attributes that emerge as significantly related to hospitals' attractiveness are different. Finally, potential applicants have more favorable perceptions of both instrumental and symbolic attributes than employed doctors. Practical and theoretical implications deal with how hospitals should audit their employer image and manage their employer branding practices.